2023
DOI: 10.1093/isq/sqad026
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Characteristics of Foreign Investment Screening Mechanisms: The New PRISM Dataset

Abstract: Since the 2008 financial crisis, many advanced industrialized economies, while eager to attract foreign direct investment (FDI), have also implemented or tightened investment screening mechanisms (ISMs), which empower governments to restrict foreign takeovers. ISMs, at the nexus between international political economy and international security, are an understudied phenomenon, although they have recently gained in policy prominence worldwide as a result of emerging technological risks and new threat actors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…What is novel about contemporary ISMs is their security, not economic, dimension (Bauerle Danzman & Meunier, 2023). The new regimes that have been recently created or tightened are aimed at reviewing the essential security interests that inward investment may negatively affect.…”
Section: What Is Investment Screen Ingmentioning
confidence: 99%
See 1 more Smart Citation
“…What is novel about contemporary ISMs is their security, not economic, dimension (Bauerle Danzman & Meunier, 2023). The new regimes that have been recently created or tightened are aimed at reviewing the essential security interests that inward investment may negatively affect.…”
Section: What Is Investment Screen Ingmentioning
confidence: 99%
“…Table 1 provides an overview of the features of EU member states' ISMs (Bauerle Danzman and Meunier, 2023). Several descriptive features stand out.…”
Section: Investment Screen Ing In the Eu: Descrip Tive Pat Ternsmentioning
confidence: 99%
“…A diverse mixture of state-owned enterprises and sovereign wealth funds are emulating the strategies of private firms and increasingly engaging in M&A activity to generate financial returns, support long-term prosperity and access strategic industries, among other motivations (Alami and Dixon, 2022; Babic et al, 2020). At the same time, the proliferation of inward foreign investment screening shows how some nation-states are simultaneously slowing down global M&A activity (Danzman and Meunier, 2023). As M&As facilitate the movement of corporate power, they are not politically neutral.…”
Section: Financialization and The Role Of Intermediariesmentioning
confidence: 99%
“…As M&As facilitate the movement of corporate power, they are not politically neutral. M&As are intimately entwined with geopolitical relations, and nation-states increasingly screen and scrutinize deals in order to ensure that potential takeovers do not pose risks to national security or undermine their wider geostrategic economic objectives (Alami, 2023; Danzman and Meunier, 2023). Researching M&As can therefore generate important insights into the uneven financialization of nation-states.…”
Section: Financialization and The Role Of Intermediariesmentioning
confidence: 99%
“…Political forces critical of economic globalization have been on the rise over the past decade (Bisbee et al, 2020;Milner, 2021;Walter, 2021). Inward-looking economic strategies are spreading rapidly (Bauerle Danzman & Meunier, 2023;Meunier & Nicolaidis, 2019), and the American-led liberal international order is said to be in crisis (Lake et al, 2021;Trubowitz & Burgoon, 2020). Accordingly, many analysts have suggested that we have entered a period of "deglobalization" in which multinational corporations (MNCs) are in retreat as states reassert their control and production networks are being reshored.…”
Section: Introductionmentioning
confidence: 99%